2008
DOI: 10.1152/japplphysiol.00865.2007
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant proteins B and C are both necessary for alveolar stability at end expiration in premature rabbits with respiratory distress syndrome

Abstract: Modified natural surfactant preparations, used for treatment of respiratory distress syndrome in premature infants, contain phospholipids and the hydrophobic surfactant protein (SP)-B and SP-C. Herein, the individual and combined effects of SP-B and SP-C were evaluated in premature rabbit fetuses treated with airway instillation of surfactant and ventilated without positive end-expiratory pressure. Artificial surfactant preparations composed of synthetic phospholipids mixed with either 2% (wt/wt) of porcine SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 40 publications
4
68
0
1
Order By: Relevance
“…SP-A and SP-D are high molecular weight hydrophilic proteins, that play a role in the innate immune response [12]. In contrast, SP-B and SP-C are small hydrophobic proteins that facilitate formation and stabilization of the surfactant film [13].…”
Section: Introductionmentioning
confidence: 99%
“…SP-A and SP-D are high molecular weight hydrophilic proteins, that play a role in the innate immune response [12]. In contrast, SP-B and SP-C are small hydrophobic proteins that facilitate formation and stabilization of the surfactant film [13].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of surface activity by CBS. Surface activity of surfactant samples was measured by CBS; developed and built by Schürch and Bachofen (19) as previously described (20,21). The test chamber was initially filled with 10% sucrose in saline.…”
Section: Methodsmentioning
confidence: 99%
“…The V tissue was calculated by converting the wet weight of the lung into a volume by dividing the wet weight by the specific density of lung tissue. Lung weight and V lung were determined in separate series of experiments and the method is described elsewhere (20,26).…”
Section: In Vivo Studymentioning
confidence: 99%
“…SP-C is lipid membrane-associated and thus probably performs its surface activity in a concerted manner. And it improves surfactant activity in particular interfacial adsorption, film stability and its respreading abilities (Cruz et al, 2000;Serrano and PerezGil, 2006;Wang et al, 1996), and it has been shown that these roles are particularly relevant at extensive lung expansion and relaxation during periods of high ventilatory demands (Almlén et al, 2008). Therefore, this study was designed to evaluate the effects of LPS on its induced apoptosis and SP-C expression inhibiting activity and its possible mechanisms using the primary cultured rat AEC II cells as the experimental model.…”
Section: Introductionmentioning
confidence: 99%